MEDIA MIND MAPPING UNTUK MENINGKATKAN PEMAHAMAN MATERI KALIMAT BERPOLA - Indriana Puspita Dewi; Aninditya Sri Nugraheni (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This study aims to determine the effect of using mind mapping media on patterned sentence material on the understanding of SMA/SMK/MA equivalent students. This research is a quantitative research. The research method used is One Group Pretest-Posttest Design. The population in this study were SMA/SMK/MA equivalent students. The sampling technique used was the snowball sampling technique. Samples were obtained from disseminating from small groups to large groups. The data collection instrument used was multiple choice test sheets which were given through pre-test and post-test via google form and WhatsApp to provide mind mapping media. The data from this study were analyzed using descriptive statistics by analyzing the mean, median and mode obtained from the pre-test and post-test. From the research results, it is known that the average, median and post-test mode results after being given mind mapping media are more improved than before being given mind mapping media by doing a pre-test. So it can be concluded that there is a significant effect after the use of mind mapping media with patterned sentence material on the understanding of SMA/SMK/MA students on an equal footing.